Motivasi Menjadi Nasabah Bank Syariah DitinjauDari Keikutsertaan Kuliah Ekonomi Islam(Penelitian Pada Mahasiswa Pendidikan AkuntansiFakultas Keguruandan Ilmu PendidikanUniversitas Muhammadiyah SurakartaTahun 2015/2016 ) - Wahyuningsih, Wahyuningsih, Drs. Muhammad Yahya, M.Si (2016)
The purpose of this study was the effect of the participation of Islamic economics courses on motivation to become customers of Islamic banks. This type of research is quantitative descriptive research. The research sample is 114 students education Keguruandan Accounting Faculty of Education Sciences University of Muhammadiyah Surakarta Year 2015/2016. The data collection instruments such as questionnaires and documentation. Before the questionnaire used first questionnaire tested for validity and reliability levels. Data analysis techniques used in this research is the analysis of simple linear regression, t test. The results of the analysis of simple linear regression between Y = 234.764 + 0.829 X. The conclusion that can be drawn is that there does participation of 2 Islamic economics lecture on motivation to become customers of Islamic banks showed H_0 rejected. This is proven by testing hypotheses (t test) in which it is known that T_ (count)> T_ (table) that T_ (15.322)> T_ (1,981).